Curcumol Suppresses CCF-Mediated Hepatocyte Senescence Through Blocking LC3B–Lamin B1 Interaction in Alcoholic Fatty Liver Disease - Qi, Xiaoyu; Zheng, Shuguo; Ma, Mingyue; Lian, Naqi; Wang, Hongting; Chen, Lerong; Song, Anping; Lu, Chunfeng; Zheng, Shizhong; Jin, Huanhuan (Frontiers in Pharmacology, 2022)
Recent studies indicated that hepatocyte senescence plays an important role in the development of alcoholic fatty liver disease (AFLD), suggesting that inhibition of hepatocyte senescence might be a potential strategy for AFLD treatment. The present study investigated the effect of curcumol, a component from the root of Rhizoma Curcumae, on hepatocyte senescence in AFLD and the underlying mechanisms implicated. The results showed that curcumol was able to reduce lipid deposition and injury in livers of ethanol liquid diet fed mice as well as in ethanol-treated LO2 cells. Both in vivo and in vitro studies indicated that supplementation with curcumol effectively alleviated ethanol-induced cellular senescence as manifested by a decrease in senescence-associated β-galactosidase (SA-β-gal) activity, a downregulated expression of senescence-related markers p16 and p21 and a dysfunction of telomere and telomerase system. Consistently, treatment with curcumol led to a marked suppression of ethanol-induced formation of cytoplasmic chromatin fragments (CCF) and subsequent activation of cGAS-STING, resulting in a significant reduction in senescence associated secretory phenotype (SASP)-related inflammatory factors secretion. Further studies indicated that curcumol’s inhibition of CCF formation might be derived from blocking the interaction of LC3B with lamin B1 and maintaining nuclear membrane integrity. Taken together, these results indicated that curcumol was capable of ameliorating AFLD through inhibition of hepatocyte senescence, which might be attributed to its blocking of LC3B and lamin B1 interaction and subsequent inactivation of CCF-cGAS-STING pathway. These findings suggest a promising use of curcumol in the treatment of AFLD.